Successful treatment of an elderly patient with relapsed/refractory angioimmunoblastic T-cell lymphoma with the PI3Kδ inhibitor linperlisib: a Case Report - Chu, Ming-Qiang; Zhang, Ting-Juan; Yang, Qian; Feng, Yuan; Lu, Chao; Ji, Yong-Hui; Qian, Jun; Zhou, Jing-Dong (Frontiers in Pharmacology, 2025)
Angioimmunoblastic T-cell lymphoma (AITL), a highly aggressive peripheral T-cell lymphoma (PTCL), carries a poor prognosis in elderly patients due to frequent relapse and limited salvage options after multiline therapy. We present the case of an 80-year-old woman with relapsed/refractory (R/R) AITL who relapsed after CHOP and exhibited resistance to the following sequential therapies: second-line chidamide plus COP and third-line chidamide with mitoxantrone hydrochloride liposome. Molecular analysis revealed DNMT3A and IDH2 mutations, reflecting disease complexity. Salvage therapy with linperlisib, a selective PI3Kδ inhibitor, combined with gemcitabine/oxaliplatin induced sustained partial remission, followed by linperlisib maintenance. The regimen demonstrated exceptional safety, with no grade ≥2 toxicities, even in this frail population. This case highlights the dual role of linperlisib as an effective and well-tolerated therapy for elderly R/R AITL patients who have exhausted prior lines. By precisely targeting PI3Kδ, our findings offer critical real-world evidence to address the unmet need for safe salvage strategies in this vulnerable population.